(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study was performed to investigate the effects of job satisfaction and burnout on nursing service quality in long-term care hospital. Methods/Statistical analysis: Participants were 120 nurses working at 10 long-term care hospitals. Data were collected from August to September, 2017. The collected data were analyzed using SPSS 22.0 Findings: Job satisfaction was different according to total clinical experience, career in present hospital, and monthly income. Burnout was different according to age, marital status, total clinical experience, monthly income, and pattern of shift. Nursing service quality was different according to monthly income, and pattern of shift. There were significant correlations among job satisfaction, burnout and nursing service quality. Factor influencing nursing service quality was burnout and explanatory power was 33.6%. Improvements/Applications: In order to improve the nursing service quality, it is important to create an environment where nurses can work long-term and reduce burnout.